Dampak Nilai Perusahaan dengan Ukuran Perusahaan sebagai Variabel Moderasi pada Sektor Makanan dan Minuman di Bursa Efek Indonesia - Elvina Nadya Aprilianda; Dhani Ichsanuddin Nur (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
Firm value is an important indicator for investors to evaluate the company as a whole before investing in a company. This study aims to determine whether profitability, capital structure and company size as a moderation effect on firm value in food and beverage companies listed on the IDX. This study uses quantitative research. The research sample used a purposive sampling technique consisting of 24 companies. The analytical method used is Moderated Regression Analysis (MRA). The results of the study show that Profitability and Capital Structure can contribute to increasing the value of the Company. Firm size is able to moderate profitability and capital structure in increasing firm value. Keywords: Profitability; Capital Structure; The value of the company; Company Size